Service quality versus service excellence: a paradigm shift - Kasim, Rozilah; Umar, Muhammad Akilu; Juanil, David Martin Daud (American Scientific Publishers, 2018)
Service users are continuously recognised as a medium for appraising the level of services provided by the local governments. The achievement of service excellence is dependent upon service user experience which is considered as a mechanism that provides a basis for a paradigm shift from service quality to service excellence in Malaysian local governments. The aim of this paper is to establish the difference between service quality and service excellence in the context of service delivery by clearly distinguishing the two practices. This can be achieved through examining the existing practice of services quality which is to provide satisfaction to the service user and the scope of operation of service excellence. In order to understand the true position of the service users with regards to service delivery and to clearly distinguish between service quality and service excellence (SERVEXCEL). Furthermore, to establish the need for a shift from service quality to service excellence which is relatively a new paradigm in Malaysian service perspective. More than one hundred academic papers and materials were reviewed from the background of service quality and service excellence from which fifty-one was found to be more relevant to the phenomenon understudy. Service excellence provides what is known as service delight because it is basically designed to focus on the needs of the service user. Therefore, both private and public institutions can benefit from this practice which can enhance the level of services provided. The motive for research is to further establish a link between service quality and service excellence with the latter having more value creation so as to achieve service excellence through user experience. The local government councils in Malaysia serves as application site for the research. It is concluded that service excellence starts where service quality stops and it offers a resounding prospects for the future conduct of service delivery. It also provides an area of research in the field of services provided primarily by the local governments.